2015
DOI: 10.1016/j.apnr.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–Infant interaction in women with unipoloar and bipolar depression

Abstract: Background One percent of women experience bipolar disorder and are likely to suffer from mood disorders during the postpartum period, potentially impacting interaction with their infants. The purpose of this study was to describe maternal infant interactions in women with bipolar depression at 12 months postpartum and to compare interactions to women with unipolar depression and a control group. Methods Using a descriptive design, maternal infant interactions in women with bipolar disorder (n=40) were video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
(12 reference statements)
4
12
2
Order By: Relevance
“…One paper published after the systematic review was finished [51] showed that women with BD had lower scores on maternal-infant interaction at 12 months postpartum; this is an area that would benefit from further study. Marengo et al [52], also published after the systematic review was finished, highlighted results related to reproduction decisions of women with BD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One paper published after the systematic review was finished [51] showed that women with BD had lower scores on maternal-infant interaction at 12 months postpartum; this is an area that would benefit from further study. Marengo et al [52], also published after the systematic review was finished, highlighted results related to reproduction decisions of women with BD.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-eight papers were found in PubMed in this second search and no papers in the Cochrane Library. Four new papers [5154] were found to be topical for this review. Logsdon et al 2015 [51] described maternal-infant interaction at 12 months postpartum in women with BD compared to women with unipolar depression and a control group without a major mood disorder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the first year, impairments in maternal behaviour, such as reduced sensitivity, have been demonstrated among mothers with BD (Hipwell et al 2000 ; Hipwell and Kumar 1996 ). Studies have also reported non-significant trends of decreased infant expressivity (Hipwell et al 2000 ) and dyadic reciprocity (Logsdon et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…While many mothers with bipolar disorder would like to breastfeed, most mothers with postpartum psychosis or bipolar disorder require treatment with psychotrophic medications, especially antipsychotics and mood stabilizers. In addition, maternal psychiatric disturbances during the postpartum period negatively influence not only mothers but also mother−infant relationships and child−mother attachment, and can lead to suicidal and infanticidal behaviors, especially if there are psychotic features . On the other hand, the benefits of breastfeeding should be carefully balanced against the deleterious effect of sleep deprivation in triggering mood episodes .…”
mentioning
confidence: 99%